Soil trafficability and vehicle mobility - Shen, Weiyue. (2008)
This report consists of two parts: Part one and Part two. These two parts deal with two different topics. The part one is on soil trafficability and the part two on the numerical modeling of pile groups. In the part one, remote sensing technique on soil trafficability assessment is first discussed, which includes the literature review and research plan on the topic. The next subject in part one is the soil-vehicle interaction. This includes the research plan of carrying out characterization of soils in the region and investigating the effect of soil remolding from vehicle loading on soil trafficability. In the part two, the variational solution procedure has advantages over existing methods like the boundary element method and is an efficient approach for solving the three-dimensional problem of laterally or vertically loaded pile groups.